Advanced MRI applications and findings of malignant phyllodes tumour: review of two cases - Idrus Alhabshi, Sharifah Majedah; Rahmat, Kartini; Abu Hassan, Hasyma; Westerhout, Caroline Judy; Chandran, Patricia Ann (Springer Japan KK, 2013)
Phyllodes tumour or cystosarcoma phyllodes is a rare stromal breast tumour that is usually benign but on rare occasions can turn malignant. Non-specificity of the imaging features on sonography and mammography makes it difficult to distinguish malignant from benign counterparts solely based on imaging. The final diagnosis is still highly dependent on histopathological assessment. Herein, we describe two cases of malignant phyllodes tumour with emphasis on magnetic resonance (MR) imaging features using advanced MR applications.